Distribution and Antibiotic Resistance of Streptococci and Enterococci Isolated from Dental Caries and Healthy People - Shahad Fadhil Al-Taie1; Muna T. Al- Musawi2; Zaid S. Rasheed3 (Journal of Medical Microbiology and Infectious Diseases)
Introduction: Antimicrobial resistance is one of the most significant challenges globally that threatens our ability to treat infectious diseases. This study investigated Streptococci and Enterococci in dental caries and healthy individuals and determined antibiotic resistance in the recovered bacteria. Methods: One hundred and twelve samples were collected, 56 from patients with dental caries and 56 samples from the teeth and saliva of healthy people. The samples were cultured on blood agar and purified on Mitis Salivarius agar. All isolates were identified by biochemical tests and Vitek 2 system and then examined for antibiotic susceptibility by disc diffusion method. Results: Streptococci and enterococci were the most isolated agents from dental caries and the teeth and saliva of healthy people. Streptococcus spp. comprised 48.61% of bacteria in dental caries and 28.40% in healthy individuals, while Enteroccus spp. was 22.22% in dental caries and 30.84% in healthy individuals. Streptococcus mutans and Streptococcus salivarius were more prevalent in dental caries and healthy individuals, respectively, while Enterococcus faecium was detected in both dental caries and healthy individuals. Also, there were significant differences between the number of streptococci isolated from healthy and caries people (P<0.05). In isolates recovered from healthy people, the streptococcal spp. exhibited high resistance to azithromycin (82.6%), cefixime and tetracycline (91.3%), and amoxicillin (60.8%). In contrast, enterococci were resistant to tetracycline (92%) and cefixime (76%). In dental caries isolates, the streptococcal and enterococcal spp. showed the highest resistance to amoxicillin (> 68%). Conclusions: The streptococcal and enterococcal spp. comprised the most isolated bacteria from healthy individuals and dental caries and exhibited multidrug resistance.